Biomaterials for the rehabilitation of bone and teeth tissues from the sequelae of oral trauma - Mayra de la C Pérez Álvarez; Amisel Almirall La Serna (Open Journal of Trauma - Peertechz Publications, 2020)
Diagnosis and treatment for traumatic dental injuries are very complex due to the multiple trauma entities represented by six luxation types and nine fracture types affecting both the primary and permanent dentitions. When further considering that fracture and luxation injuries are often combined, and can involve either dentitions, a great number of trauma scenarios may result [1]. Classifications, epidemiological, clinical and radiographic studies are considered very important to evaluate the particular case in each patient in order to correctly plan and conduct the treatments of these injuries. Therefore, even though oral-facial trauma has been extensively investigated, in vivo clinical essays are frequently needed to understand and improve the healing processes after trauma and to determine the best treatment in each case [2,3].